Cross-cultural validation of the Arabic version of the Dry Eye Questionnaire-5 (DEQ-5) scale - Bouazza, Samira; Abbouyi, Samira; Ragala, Mohammed El Amine; El Hilaly, Jaouad; El Rhazi, Karima; Zarrouq, Btissame (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The Dry Eye Questionnaire-5 (DEQ-5) and the Ocular Surface Disease Index (OSDI) are recommended scales by TFOS DEWS II Diagnostic Methodology report to apprehend patients with symptoms of dry eyes. Before their use, these scales must undergo a cross-cultural adaptation to the target population. The purpose of this work is to validate the Arabic version of the DEQ-5.Methods: Forward-backward translation process was used. The reliability of the Arabic DEQ-5 was computed with Cronbach α. Discriminant validity of DEQ-5   was explored by analysis of variance with the Arabic version of the OSDI (Arabic OSDI) used as gold standard. The concurrent validity was examined by Pearson's correlation coefficient, receiver operating characteristic (ROC) curve was generated, and the cut-off of the Arabic DEQ-5 was produced. Rasch model and Exploratory Factor Analysis were performed to explore its dimentionality.Results: The Arabic DEQ-5 met the Rasch analysis criterion of unidimensionality with an eigenvalue of the first contrast of 1.7, measurement precision of 2, and reliability of 0.8. The average scores measured by Arabic DEQ-5 in the 4 categories defined by Arabic OSDI were significantly different from each other (F=26.20, d=3, P